Characteristics of Ulul Albab: A Study of Academic Ethics In Islamic Education - Widaningsih, Sri; Kusmiat, Erni (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the character of ulul albab as a study of academic ethics in Islam. This type of research uses a qualitative approach with library research methods. Data sources are quoted from credible websites such as Google Scholar and SINTA. Furthermore, the data was analyzed and checked for validity through data triangulation. The results of this research conclude that there are 9 ulul albab characters as a complete form of academic ethics for every student, namely (1) having knowledge and being serious about developing it; (2) firm attitude in the practice of scientific culture; (3) visionary in balancing logical thinking and Islamic spirit; (4) have an integral-transdisciplinary view; (5) has a high work ethic and self-devotion attitude to the community; (6) pious and noble, and emulate the Prophet Muhammad; (7) have a moderate attitude; (8) contribute to the development of human civilization; and (9) looking happy or sa'adah in dealing with life.